High-resolution UAV Orthomosaic and DSM Dataset - Aklavik, NWT, CA 10 cm GSD [2022, 2024] - Mueller, Marlin M.; Thiel, Christian; Kaiser, Soraya; Lenz, Josefine; Langer, Moritz; Fritz, Oliver; Marx, Sabrina (2025)
This dataset comprises a high-resolution (10 cm) Orthomosaic and Digital Surface Model (DSM) generated from aerial imagery captured by a DJI Mini 2 drone during two acquisition campaigns in September 2022 (20220919 - 20220921) and March 2024 (20240322 - 20240324). The data covers an area of 2.37 km² and focuses on the town/village itself, providing detailed elevation and visual information about the built environment and surrounding terrain. The 2024 dataset was aligned to the 2022 dataset using the Iterative Closest Point (ICP) registration algorithm, achieving a median vertical offset of 5.76 cm. This alignment ensures consistency and facilitates change detection analysis between the two acquisition periods. The processing parameters used in Agisoft Metashape are detailed in the attached reports. This dataset was acquired as part of the UndercoverEisAgenten project, funded by the German Federal Ministry of Education and Research in collaboration with students from Moose Kerr School in Aklavik, NWT, Canada.